A Cultural Acculturation: The Code-Mixing and Language Meaning in ‘Geef Mij Maar Nasi Goreng’ Song - Sari, Fransiska Marta; Sri Utami; Nensy Megawati Simanjuntak (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This research explores the phrase "Geef Mij Maar Nasi Goreng" from the song of the same name by Aunt Lien as a lens into cultural acculturation between Indonesia and the Netherlands. By employing critical discourse analysis, the study investigates how the phrase reflects code-mixing, conveys cultural meaning, and contributes to identity construction. The research found that the phrase is a microcosm of cultural intersection, combining Dutch and Indonesian languages to express longing for Indonesian cuisine. It symbolizes the challenges of adapting to a new culture while maintaining one's heritage. Moreover, the song acts as a platform for Aunt Lien to navigate her Dutch-Indonesian identity, contrasting Indonesian flavors with Dutch culinary staples. Ultimately, the phrase serves as a potent symbol of the complexities of acculturation, demonstrating how language can be a vehicle for both connection and disconnection between cultures. This study contributes to understanding the role of language in cultural exchange and the experiences of individuals navigating multiple cultural identities